UTILIZATION OF FINANCIAL ANALYSIS IN MANAGEMENT OF LARGE-ACREAGE FARM IN YEARS 1996-1999 - Spiak, Jan (Acta Scientiarum Polonorum. Oeconomia, 2002)
Moved investigation in large-acreage farm being one-man company AWRSP in years 1996-1999 dust on aim qualification of financial situation and property’s enterprise. Utilization of method of economic analysis in range of opinion of changes of structure of production, efficiencies of factors of production and financial efficiencies permitted onto looking for relationships reason - consecutive got results. Results of investigations confirmed, that at small changes in structure production and decrease of coefficients of efficiency of factors of production, worsen of ability stepped out to generating he carried out profit, which in 1999 year 50 zl/ha of agricultural uses. Realization of conservative strategy in productive activity caused limitations of size of money stream from operating activity also.